Cytology Slides for Molecular Analysis Can Address Both Interobserver Variability and Sample Heterogeneity: Overview of Thyroid Molecular Testing. Issue 1 (January 2019) - Narick, Christina M.; Toney, Nicole A.; Kumar, Gyanendra; Finkelstein, Sydney D.
Abstract : Abstract: Studies have shown that a high degree of inter and intraobserver variability, in addition to the heterogeneity of the sample itself, can inhibit the accuracy of cytopathological assessment of thyroid nodules. Guidelines have recommended the use of molecular analysis, used in conjunction with cytology, to assist in the guidance of patient management. Currently, there are several commercially available molecular tests offered to better assess overall malignancy risk, each now with updated and expanded capability. The collaboration between molecular pathology and cytopathology is critical to better understand the biology of these lesions and help clinicians optimize patient management and surgical decisions.